2020
DOI: 10.3390/pr8060683
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effect of Granulation and Milling Process Parameters on the Quality Attributes of Milled Granules

Abstract: Milling is an essential unit operation used for particle size reduction in solid oral dosage manufacturing. The breakage of particles in a comil is due to the intense shear applied on the particles between impeller and the screen. Breakage also occurs due to the impact from a rotating impeller. Particles exit the mill based on their size relative to the aperture size of the screen bores. This study was set up to understand the working of the comil better. A new CPP (Critical Process Parameter), in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
(43 reference statements)
1
8
0
1
Order By: Relevance
“…[ 58 ] One more reason for this trend could be the difference in the fine particles present in the input particles to the mill. Kotamarthy et al [ 48 ] observed that fine particles present in the input feed to the mill escape the mill during the quasi‐static regime operation of the mill, this regime is followed by the impact regime which governs the majority of the breakage. From Figure 5B it can be observed that, Runs 2, 3, 4, and 5, (all have a peak in the fines region [around 150 μm]), like the input “LLL” batch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 58 ] One more reason for this trend could be the difference in the fine particles present in the input particles to the mill. Kotamarthy et al [ 48 ] observed that fine particles present in the input feed to the mill escape the mill during the quasi‐static regime operation of the mill, this regime is followed by the impact regime which governs the majority of the breakage. From Figure 5B it can be observed that, Runs 2, 3, 4, and 5, (all have a peak in the fines region [around 150 μm]), like the input “LLL” batch.…”
Section: Resultsmentioning
confidence: 99%
“…where f cont is the ratio of the holdup to the maximum capacity of the comil. From previous experimentation [48] and prior knowledge, it was estimated that 1 kg of granules was the maximum capacity of the comil. Both the batch and continuous milling energy models were combined with developed PBMs to obtain the final GSD as seen in Section S1c.…”
Section: Comil Energy Modelmentioning
confidence: 99%
“…For a scalable production process, a high-speed mixer is a high-efficiency equipment that can mix different powder materials and granulates in one procedure. During the dry mixing stage, the cohesive powder components had to be disagglomerated to obtain a high degree of mixing [21,22]. Nonuniformity may occur in a certain period during the mixing process that needs to be accurately determined.…”
Section: Determination Of the Mixing Time And The Drying Time Of Granulesmentioning
confidence: 99%
“…The impeller speed range was 100-1500 rpm and the chopper speed range was 1000-3000 rpm. A dry mixing time of approximately 6 min was suggested by the machine manufacturer [21,22]. This was true for selecting the mixing time and mixing speed on the high-speed mixer.…”
Section: Determination Of the Mixing Time And The Drying Time Of Granulesmentioning
confidence: 99%
“…La molienda es una operación unitaria ampliamente utilizada en la industria minera, farmacéutica, agricultura, papel y de alimentos, la cual permite reducir el tamaño de piezas grandes a partículas pequeñas con un tamaño definido, mediante la aplicación de golpes, presiones de cizallamiento o corte (1)(2)(3). En el área de los alimentos, esta técnica se ha utilizado desde la antigüedad por los primeros homínidos que utilizaban herramientas de piedra para cortar principalmente granos, raíces y madera, hasta la actualidad mediante el uso de máquinas industriales que permiten obtener productos más elaborados como harinas, balanceados, alimentos instantáneos, entre otros (4-6).…”
Section: Introductionunclassified